2016
DOI: 10.4103/0019-5154.193670
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of topical 10% potassium hydroxide and 30% trichloroacetic acid in the treatment of plane warts

Abstract: Background:Warts are benign proliferations of skin and mucosa caused by the human papillomavirus (HPV). Plane warts are caused by HPV types 3, 10, 28, and 41, occurring mostly in children and young adults. Among the treatment modalities, topical application of trichloroacetic acid (TCA) is age old. Potassium hydroxide (KOH) has a keratolytic effect on virus-infected cells. It is less irritating, less painful, less scar forming, and can be safely used in children too. Hence, it could be a better topical agent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… Types of human papillomavirus (HPV) that cause plane warts and other subgroups of beta-papillomaviruses are more common among immunocompromised persons, especially those who have been on organ transplant waiting lists (15).  Extremely severe or long-lasting warts may raise concerns about a potential immune deficiency since they might be the first sign of less severe immunosuppressed conditions including lymphoma, idiopathic CD4 lymphocytopenia, or HIV infection (16).  Treatment  Several potential therapies are being explored (13).…”
Section:  Pathogenesismentioning
confidence: 99%
“… Types of human papillomavirus (HPV) that cause plane warts and other subgroups of beta-papillomaviruses are more common among immunocompromised persons, especially those who have been on organ transplant waiting lists (15).  Extremely severe or long-lasting warts may raise concerns about a potential immune deficiency since they might be the first sign of less severe immunosuppressed conditions including lymphoma, idiopathic CD4 lymphocytopenia, or HIV infection (16).  Treatment  Several potential therapies are being explored (13).…”
Section:  Pathogenesismentioning
confidence: 99%
“…Local destructive methods are used more often than immunomodifiers . They include cryotherapy [ 15 ], trichloroacetic acid [ 16 ], lactic acid, salicylic acid, electrosurgery, curettage, surgery with scalpel or scissors [ 17 ], photodynamic therapy [ 18 ], and various types of lasers [ 17 ]. In a Cochrane review done in 2003 by Gibbs et al [ 19 ], cryotherapy was reported to be the most commonly used therapy for warts.…”
Section: Introductionmentioning
confidence: 99%